A162 PHYSICIAN DIAGNOSES AND SELF-DIAGNOSIS OF PATIENTS WITH CELIAC DISEASE IN THE INTERNET ERA. (1st March 2018) - Hansen, T; Silvester, J; Rigaux, L; Graff, L A; Bernstein, C N; Walker, J R; Duerksen, D
Abstract: Background: Celiac disease (CD) is an immune condition defined by intestinal inflammation in response to gluten. Manifestations of CD are variable and diagnostic delays are common. With growing public awareness of CD, many individuals are turning to resources such as the Internet, family and friends for health information. Aims: In a population of newly diagnosed CD subjects, identify: 1. Alternate diagnoses prior to CD diagnosis 2. Resources used to self-diagnose CD 3. The role of the Internet in directing the diagnosis of CD Methods: Between July 2014 and February 2017, adults with positive TTG and/or EMA antibodies and Marsh III histology were prospectively enrolled in the Manitoba CD Cohort. The initial study visit (within 6 weeks of initiating a gluten-free diet) included an optional online survey with items related to symptoms, use of health information sources and diagnoses given prior to CD. Results: Among 99 subjects who completed the survey, median symptom duration was 3 years (IQR 1–10) prediagnosis and 1 year (IQR 0.25–3) prior to seeking health care evaluation. The most common symptoms at diagnosis were gas (58%), urgency (45%) and difficulty concentrating (35%). Many subjects (35%) were given a diagnosis other than CD for their symptoms, most commonly IBS or a psychological diagnosis (Table 1). The Internet and family doctor were considered the most important sources used to identify a diagnosis. About 80% of subjects who were Internet users (n=93) used the Internet to research their symptoms. The most accessed Internet sites were the Canadian Celiac Association (n=55), Mayo clinic (n=52) and WebMD (n=39). One quarter (n=18) made a self-diagnosis based on their search, with 7 concluding that CD was the most likely diagnosis. As a result of their Internet search, 66% talked to a friend, 54% saw their family doctor, and 43% changed their diet. Doctors visits were used to ask for a TTG (31%), discuss what was found on the Internet (27%) and/or ask for a gastroenterology referral (24%). Conclusions: Many doctors and patients attribute symptoms of CD to alternate conditions, which may contribute to diagnostic delays. Many individuals diagnosed with CD used the Internet to research their symptoms thereby initiating the CD evaluation. More work is needed to raise awareness about CD screening. Funding Agencies: None